Pizza and Taco : go viral! - Shaskan, Stephen (Pizza and Taco, 2026)
Inspired by other food besties' channels, best friends Pizza and Taco borrow Ms. Banana's uncooperative dog, Biscuit, in an attempt to go viral on StewTube.